An explanation for experimental behavior of hybrid metallocene silica-supported catalyst for ethylene polymerization - Aguiao Rodrigues, Silvia (2004)
This work presents the results of homopolymerization of ethylene using an hybrid system (nBuCp)2ZrCl2-Cp2ZrCl 2, supported on silica. The catalytic systems were analyzed by RBS, DRIFTS and EXAFS and polyethylenes (PE) by GPC and DSC. The catalytic activities and the polymer properties showed dependence on the different ratio used (nBuCp)2ZrCl2/Cp2ZrCl2 at the preparation step. Theoretical studies permit us to conclude that the metallocenes interact with the surface in different ways. Depending on the addition order and the molar ratio between both metallocenes, distribution and nature of active species would be different. Possibility of binuclear active sites with different propagation and termination constants is analyzed and discussed. EHMO calculations allow us to conclude that Cp2ZrCl 2 has a strong affinity by AIS plane, whereas (nBuCp) 2ZrCl2 shows similar affinity for both silica planes.